Hukum Pidana terhadap Pemaksaan Anak sebagai Pengemis terkait Undang-Undang Kesejahteraan Anak - Nabila Dwi Elsa (University of Merdeka Malang, 2022)
Regarding the increasing number of underage beggars, it is motivated by individuals who force children to work as beggars by instilling in children that working is easier and earning money than taking proper education in accordance with their rights as children, as stated in Article 5 paragraph (1) The Child Protection Act, which states